Epidural ropivacaine combined with fentanyl or in combination with clonidine in infraumblical surgeries: a comparative study - Singh, Rakesh Bahadur; Singh, Dheer; Mishra, Prashant K.; Kumar, Manoj; Kumar, Virendra (International Journal of Research in Medical Sciences, 2017)
Background: The addition of an adjuvant, like clonidine and fentanyl, in epidural blockade has enhanced the effectiveness of local anaesthetics as they not only help in intensifying and prolonging the blockade effect but also help in the reduction of the dose of local anaesthetics. Methods: Our study had 45 patients, all patients belonged to ASA grade-I or II, between 20 and 55 years of age requiring neuraxial blockade for lower abdominal surgeries. All the patients were randomly allocated into two groups. Group-I: Epidural ropivacaine 0.75% (14.5ml) + Fentanyl 50 µgm (1 ml) + 0.5 ml distilled water. Group-II: Epidural ropivacaine 0.75% (14.5ml) + Fentanyl 50 µgm (1 ml) + clonidine 50 µgm. Patients were monitored for sensory and motor blockade, hemodynamic parameters, rescue analgesia and adverse effects in perioperative period. Results: Highest level of sensory and motor blockade was found to be insignificant (p>0.05) in both the groups. Mean time for regression of sensory blockade to T10 was significantly longer (p<0.05) in group II as compared to group I. The duration of motor blockade was significantly (p<0.001) higher in patients of Group-II as compared to Group-I. The addition of clonidine to epidural Ropivacaine and fentanyl (Group-II) produces longer duration of analgesia as compared to Group-I. Haemodynamically the patients in both the groups behaved similarly. The patients, in whom epidural fentanyl was used, had slightly higher incidence of nausea, vomiting, dry mouth and pruritus. Conclusions: So this study re-established the fact, that the fentanyl and clonidine when added as adjuvant to epidural ropivacaine, significantly prolongs the analgesic duration without causing significant hemodynamic and respiratory changes.